Progress in the clinical application of allogeneic platelet-rich plasma for diabetic foot treatment - Qin, Huijuan; Yang, Hui; Wang, Jing; Jiang, Dong; Chen, Yinchen; Wang, Wei; Wang, Aiping (Frontiers in Endocrinology, 2025)
Due to peripheral neuropathy and varying degrees of vascular disease, patients with diabetes often suffer from foot ulcers that are challenging to heal and may even progress to gangrene. In recent years, autologous platelet rich plasma (au-PRP) gel has been widely used in the treatment of chronic ulcers, including diabetes foot. However, its limitations have become increasingly evident, such as difficulties in collecting sufficient blood from patients, deficiencies in platelet count and/or function among individuals with diabetes, and high costs associated with individually required equipment. Allogeneic platelet rich plasma (al-PRP) offers similar anti-inflammatory, anti-infective, and growth promoting effects while addressing these drawbacks. Notably, al-PRP can be mass-produced into ready-to-use products, simplifying clinical applications and significantly reducing costs. This article conducted a comprehensive analysis of the application mechanism, necessity, effectiveness and safety, preparation and application methods of al-PRP in the treatment of diabetic foot ulcers, it showed that al-PRP has a promising application prospect in the treatment of diabetic foot.